Administration of Vibrio SKT-b Probiotic Bacteria on Tiger Shrimp Larvae Through Artemia Enrichment - . Widanarni; D.T. Soelistyowati; A. Suwanto (Jurnal Akuakultur Indonesia)
This experiment was conducted to study the effects of probiotic bacteria (Vibrio SKT-b) administration on tiger shrimp larvae through Artemia enrichment.  This experiment was done in two treatments; shrimp larvae fed on Vibrio SKT-b enriched Artemia and fed on Artemia without enrichment.  Enrichment of Vibrio SKT-b into Artemia rearing media used initial concentration of 106 CFU/ml.  Application of Artemia to shrimp larvae was done in fourteen days.  Growth in length and weight of shrimp larvae were observed at the beginning and at the end of the experiment; while survival rate of larvae was observed at the end of the experiment.  Growth in body length and weight of shrimp larvae fed on Vibrio SKT-b enriched Artemia were higher than control.  Survival rate were 89-93%, and insignificantly different than that of control (70-80%).